Cover Picture: In vitro diagnostic technologies for the detection of extracellular vesicles: current status and future directions (View 2/2023). Issue 2 (24th April 2023) - Song, Shuya; Zhu, Ling; Wang, Chen; Yang, Yanlian
Abstract : Extracellular vesicles (EVs) provide real‐time information about the physiological and pathological states of parental cells and are potential biomarkers for disease diagnosis. Many methods for isolating EVs from body fluids and techniques for analyzing EVs biomolecules, including protein, nucleic acids, and lipids, have emerged with potential for clinical application.